Carbon Nanotubes: Free Form Growth of Carbon Nanotube Microarchitectures on Stainless Steel Controlled via Laser‐Stimulated Catalyst Formation (Adv. Mater. Interfaces 16/2017). Issue 16 (21st August 2017) - Reinhardt, Hendrik; Hellmann, Christoph; Nürnberger, Philipp; Kachel, Stefan; Hampp, Norbert
Abstract : Norbert Hampp and co‐workers describe site‐selective carbon nanotube (CNT) growth on stainless steel, achieved by laser‐stimulated self‐organization of highly granular transition metal oxide precursors that transform into CNT catalysts upon thermal reduction, thus enabling the fabrication of free‐form CNT microarchitectures with standard chemical vapor deposition equipment, in article number1700508 . This process facilitates control over CNT location and height as well as the alignment of CNT bundles.